Integral Upbringing in the Perspective of Pedagogical Qualitative Research - Magdalena Ciechowska; Anna Walulik (Nicolaus Copernicus University in Toruń, 2018)
The article is aimed at showing the integral upbringing and its role in the pedagogical qualitative research. This kind of upbringing as an object of the pedagogical research at the same time has an impact on the subject of research - the researcher and the researched. It comes to it through the authenticity of form-teacher realizing one of its tasks - to know the pupil - the researched. If such an upbringing activity pursues to the integral development of a person in the atmosphere of mutual respect and dignity, so analogically in the qualitative research the integrity between the researcher and the researched takes place. This integrity is shown in two aspects: the research paradigm and research methods sensitive to a person.